2012
DOI: 10.3201/eid1810.120359
|View full text |Cite
|
Sign up to set email alerts
|

Human Polyomaviruses in Children Undergoing Transplantation, USA, 2008–2010

Abstract: Immunocompromised patients are at risk for disease caused by infection by some polyomaviruses. To define the prevalence of polyomaviruses in children undergoing transplantation, we collected samples from a longitudinal cohort and tested for the 9 known human polyomaviruses. All were detected; several were present in previously unreported specimen types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 12 publications
1
41
1
Order By: Relevance
“…Transfection of A549 cells with KIPyV DNA did not result in the production of infectious virus particles (our unpublished results). HPyV6 and HPyV7 DNA have been found in one nasopharyngeal aspirate sample of, respectively, a heart-transplant patient and a liver transplant patient (Siebrasse et al, 2012b). Relatively low HPyV6 and HPyV7 promoter activity was monitored in cell lines derived from the respiratory tract, suggesting that the respiratory tract may not be a genuine host tissue for these viruses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Transfection of A549 cells with KIPyV DNA did not result in the production of infectious virus particles (our unpublished results). HPyV6 and HPyV7 DNA have been found in one nasopharyngeal aspirate sample of, respectively, a heart-transplant patient and a liver transplant patient (Siebrasse et al, 2012b). Relatively low HPyV6 and HPyV7 promoter activity was monitored in cell lines derived from the respiratory tract, suggesting that the respiratory tract may not be a genuine host tissue for these viruses.…”
Section: Discussionmentioning
confidence: 94%
“…MCPyV seems to be a common skin commensal (Bellaud et al, 2014;Hampras et al, 2015;Mertz et al, 2013;Schowalter et al, 2010), but DNA is also found in blood, eyebrow hairs, tonsils, gall bladder, intestine, appendix, liver, lung, lymphoid tissue, saliva and oral samples, and urine (reviewed by Baez et al, 2013;Hampras et al, 2015;Signorini et al, 2014). HPyV6 and HPyV7 are common in skin and eyebrow hairs (Bellaud et al, 2014;Hampras et al, 2015;Schowalter et al, 2010;Wieland et al, 2014), but have in very few cases been isolated from nasopharyngeal swabs, faeces or urine (Siebrasse et al, 2012b). TSPyV resides in the skin (van der Meijden et al, 2010), but viral nucleotide sequences have also been detected in tonsillar biopsies of healthy individuals, in heart, lung, liver, spleen, bronchus, small intestine, colon tissue from a patient with myocarditis, and in renal allograft of a kidney transplant patient (Fischer et al, 2012;Sadeghi et al, 2014;Tsuzuki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of all known human polyomaviruses (with the exception of HPyV10, MWPyV, MXPyV, STLPyV and HPyV12 that were discovered later) was investigated with qPCR in 716 clinical specimens of 32 children receiving a transplant (2 lung, 11 liver, 5 heart, 2 kidney, 1 liver/lung and 11 bone marrow transplants). HPyV6 was detected in the faeces of a lung and a bone marrow transplant recipient and in a nasopharyngeal swab of a heart transplant patient; HPyV7 was found in a nasopharyngeal swab of a liver transplant patient and HPyV7 and HPyV9 in a urine sample of 2 liver transplant patients respectively (14). MWPyV and STLPyV were detected with PCR in 2.2% and 1.1%, respectively, of stool samples collected from children with diarrhoea in Saint Louis, USA (3).…”
Section: Detection In Clinical Samples With Nucleic Acid-based Methodsmentioning
confidence: 99%
“…How forehead swabs and plucked eyebrow hairs compare with respect to the number of obtained cells, viral DNA detection and load measurement requires further study. Interestingly, in a recent study, TSPyV DNA was detected in stool and nasopharyngeal swabs of a 13-year-old immunocompromised heart transplant patient 1 month after immunosuppression showing no TS symptoms, but repeated analysis in the following months remained negative (92). Occasionally also urine and kidney samples were found positive for TSPyV DNA (87).…”
Section: Clinical Samplementioning
confidence: 95%